Nucleic acid amplification techniques (NAATs) for early diagnosis of HIV-1 and HIV-2 infections - El Dib, Regina [UNESP]; Leeflang, Mariska M.G.; Mathew, Joseph L.; Almeida, Ricardo A.M.B. [UNESP]; Lewi, David S.; Kapoor, Anil; Müller, Sergio S. [UNESP]; Diaz, Ricardo S. (Wiley, 2015)
This is the protocol for a review and there is no abstract. The objectives are as follows: Our primary objective is to assess the diagnostic accuracy (sensitivity and specificity) of NAATs (both quantitative and qualitative) for early diagnosis of people of all ages with suspected HIV-1 and -2 infections. We hypothesize that their accuracy for early diagnosis will be as good as the diagnosis at a later stage. We furthermore hypothesize that there will be no differences in diagnostic accuracy between the different molecular tests when evaluated against the same reference standard. We defined early detection as a period that is consistently between one and three weeks (Busch 1997; Fiebig 2003). The secondary objective of this review is to assess the influence of sources of heterogeneity on the diagnostic accuracy of tests performed, in particular the type of HIV (HIV-1 or HIV-2), different cut-offvalues, different samples, the healthcare setting, age of the participants, differences in timing of the tests, to investigate how the time of testing relates to accuracy; and study design features.